Technological and pedagogical requirements for the functioning of the system of mixed learning in the field of higher education in Ukraine - Boychuk , Y.; Opanasenko , Y. (New Collegium, 2021)
Technologization and informatization of society create new ideas about the process of higher education and its results, which cannot be achieved in traditional education. The introduction of new technologies, the creation of information and educational environment, the involvement of active learning methods, design and distance technologies open new prospects for improving the efficiency of the educational process. At the same time, the shortcomings in using new technologies, especially distance learning, reduce the productivity of learning due to the unusualness and the need to adapt both sides of the educational process. Real communication, emotional contact, use of material objects and devices are an integral part of effective mixed education. These shortcomings can be overcome and the productivity of the educational process can be increased through the introduction of blended learning, which allows combining the advantages of traditional (full-time) and distance education, rational use of study time, increase student prepairing through the optimal ratio of online and classroom activities. Mixed learning systems have already been implemented in the West, the results of existing research confirm the high efficiency of this model of education, which opens a new space for both students and teachers, bringing the effectiveness of higher education to a new level. However, such a result is possible only if the whole list of technical and pedagogical requirements to which this article is devoted is satisfied. The article examines the basic requirements for the effective functioning of mixed learning in higher education. The components of pedagogical competence of the teacher, which are necessary for the implementation of the system of mixed learning, are identified and the potential ways of their development are given. The advantages and disadvantages of mixed learning in the current state are listed.